Spin transport in n-type 3C–SiC observed in a lateral spin-pumping device. (January 2020) - Shigematsu, Ei; Ohshima, Ryo; Ando, Yuichiro; Shinjo, Teruya; Kimoto, Tsunenobu; Shiraishi, Masashi
Abstract: 3C–SiC is a promising platform for semiconductor spintronics because it consists of light group-IV elements and has a zinc blende structure. To demonstrate spin transport in this attractive semiconductor, we conducted an experiment of spin-pump-induced spin transport through n-type 3C–SiC. A spin current is injected from Ni80 Fe20 into the SiC channel under ferromagnetic resonance of the Ni80 Fe20 . The DC electromotive force caused by the inverse spin Hall effect in an adjacent metal detector attached to the SiC is detected as a manifestation of the spin current transport. This indicates 1.2-μm-long spin transport through the n-type 3C–SiC at room temperature. This achievement is the first step in the investigation of the physics of 3C–SiC for further spintronics study and its application. Highlights: 3C–SiC is a promising candidate for a spintronic semiconductor material. Spin pumping is used for generation of spin current in 3C–SiC. 1.2-μm-long spin transport is achieved in n-type 3C–SiC at room temperature. Our results can be a great milestone for development of spintronics using 3C–SiC.